Inspector Lewis. [videorecording (DVD)] Series 8 - Whately, Kevin; Fox, Laurence; Front, Rebecca; Dexter, Colin ([Publisher not identified], 2016)
Oxford's favorite detectives Lewis and Hathaway return for the eighth and final series of the hit series. Investigating the city's most complex and intriguing crimes, Lewis clashes with the new Chief Superintendent, who questions his traditional approach. Will Lewis decide to call time on his policing career? Meanwhile, Hathaway is forced to confront his past.